STRESS MANAGEMENT TO IMPROVE PRODUCTIVITY AT BAPPEDALITBANG IN CILEGON - Pratama, Sukma; Azizah, Oktafia; Putriana, Putriana; Bilqis, Aninda Nadya; Wiguna, Wahyu (Yayasan Education and Social Center, 2024)
In the modern era, particularly within governmental environments facing high work dynamics and ambitious development targets, this study examines the role of stress management as a strategy to enhance employee productivity at Bappeda Litbang, Cilegon City. The qualitative research method uses data collection techniques, including in-depth interviews, participatory observation, and documentation studies. The results show that unbalanced workloads, role ambiguity, lack of social support, and a dynamic work environment trigger work stress at Bappeda Litbang. However, stress management strategies such as effective communication, precise task distribution, recognition, training, and managerial support can create a healthy, harmonious, and productive work environment. Employees who feel psychologically supported demonstrate motivation, loyalty, and optimal performance in achieving organisational targets. Furthermore, this study finds that active employee participation and an innovative work culture strengthen stress management and productivity effectiveness. This research recommends strengthening integrated stress management policies within the organizational culture to support sustainable and inclusive regional development.